2014
DOI: 10.3164/jcbn.14-9
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucuronidase activity and mitochondrial dysfunction: the sites where flavonoid glucuronides act as anti-inflammatory agents

Abstract: Epidemiological and experimental studies suggest that the consumption of flavonoid-rich diets decreases the risk of various chronic diseases such as cardiovascular diseases. Although studies on the bioavailability of flavonoids have been well-characterized, the tissue and cellular localizations underlying their biological mechanisms are largely unknown. The development and application of novel monoclonal antibodies revealed that macrophages could be the major target of dietary flavonoids in vivo. Using macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…The b-glucuronidase released by macrophages was shown to be essential for activation of quercetin glucuronide conjugates. Its enzymatic activity, which requires acidic pH, was promoted by increased secretion of lactate in response to mitochondrial dysfunction (Kawai, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The b-glucuronidase released by macrophages was shown to be essential for activation of quercetin glucuronide conjugates. Its enzymatic activity, which requires acidic pH, was promoted by increased secretion of lactate in response to mitochondrial dysfunction (Kawai, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, their anti-inflammatory effects are mild [35]. In addition, the relationships between their chemical structures and biological activities are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The same situation could apply for other (poly)phenols . Extracellular β‐glucuronidase secreted from macrophages and in the vascular bed can also lead to de‐conjugation of the glucuronide conjugates of (poly)phenols and deliver the aglycone at a higher local concentration, which due to its higher lipid solubility accumulates in tissues . In support of this notion, a recent acute human study reported effects of quercetin in hypertensive subjects related to increased plasma glutathione levels, an antioxidant biomarker; these effects were proportional to the bioavailability of quercetin and the rate of deconjugation of the glucuronide in tissues .…”
Section: Effects Of (Poly)phenols On Chronic Inflammationmentioning
confidence: 90%
“…It has also been postulated that inflammation enhances intracellular β‐glucuronidase leading cells exposed to glucuronide conjugates of quercetin to release the more bioactive aglycone. The same situation could apply for other (poly)phenols . Extracellular β‐glucuronidase secreted from macrophages and in the vascular bed can also lead to de‐conjugation of the glucuronide conjugates of (poly)phenols and deliver the aglycone at a higher local concentration, which due to its higher lipid solubility accumulates in tissues .…”
Section: Effects Of (Poly)phenols On Chronic Inflammationmentioning
confidence: 96%